Effect of gas blowing of A1 alloys on mechanical and technological properties of castings - A. M. Galushko; B. A. Kaledin; V. M. Korolev (Литьë и металлургия)
The article gives the results of study by mathematical planning of pilot processes of the АК7Ч and AK5M4 aluminum alloys refining with nitrogen and argon.